The urgent integration of Media Education in School curricula: a research through school newspaper production in Portugal (2005-2010) - Tomé, V.; Helena Menezes (Proceedings of the 7th Hawaii International Conference on Education, 2009)
This paper presents the outcomes of a PhD thesis that includes the design and development of multimedia tools in order to develop Media Literacy leveis in the Region of Castelo Branco, Portugal. lt also presents a research project whose main aim is to help teachers and students in the production of on-line and/or printed school newspapers.